Preparation method of tin-based babbitt metal laser cladding coating added with Ti element

By adding metal Ti powder to the tin-based babbitt alloy powder and using laser cladding technology to prepare a tin-based babbitt alloy coating, the bearing wear problem caused by insufficient hardness and wear resistance of tin-based babbitt alloy is solved, and the wear resistance and service life of the coating are significantly improved.

CN119824409APending Publication Date: 2025-04-15NANJING TECH UNIV

Patent Information

Application Number
CN202510053137.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Due to the low hardness, wear resistance and bonding strength of tin-based Babbitt alloy, it is prone to severe wear and even fall off due to the combined action of friction and shear stress under working conditions, resulting in bearing failure.

Method used

Metal Ti powder is added to the tin-based babbitt alloy powder, mixed and clad it on the surface of 20 steel by laser cladding technology to form a tin-based babbitt alloy coating containing titanium.

Benefits of technology

By refining the hard phase, the wear resistance of the coating is improved, the friction coefficient and wear rate are significantly reduced, the service life of the bearing shell is extended, and the stable operation of the bearing system is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824409A_ABST
    Figure CN119824409A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Ti-element-added tin-based babbitt metal laser cladding coating, which comprises the following steps: S1, adding a certain proportion of metal Ti powder into tin-based babbitt metal powder, adding the obtained metal Ti powder and tin-based babbitt metal powder into a mixer, and mixing for 5-6 hours to obtain composite powder; and S2, 20 steel with the size being 150 mm * 150 mm * 10 mm is selected as a base plate, the mixed powder of the tin-based babbitt metal and Ti powder is cladded to the surface of the 20 steel in a coaxial powder feeding laser cladding mode, and the tin-based babbitt metal coating added with the Ti element is obtained. According to the tin-based babbitt metal powder suitable for laser cladding, an obtained Ti-containing tin-based babbitt metal coating is compact in structure, a white hard phase is refined and evenly distributed, and good metallurgical bonding is achieved between the coating and a base material; and due to the addition of the Ti element, the wear resistance is obviously improved, and the performance of the laser cladding coating is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of laser cladding coating preparation, and in particular to a method for preparing a tin-based babbitt alloy laser cladding coating with titanium added. Background Art

[0002] Sliding bearings are composed of bearing bodies and bushings. As the key component for precise contact between the sliding bearing and the journal, the bushing is shaped like a semi-cylindrical tile with an extremely smooth surface. It is usually made of anti-friction and wear-resistant alloys with good wear resistance. Tin-based babbitt alloy is a low-melting-point bearing alloy with a hard particle phase distributed on a soft matrix. Compared with other types of bearing materials, tin-based babbitt alloy has good wear resistance, compliance and anti-seizure properties, and is recognized as the preferred material for bushings. However, given its relatively soft texture, low hardness and strength, and relatively high price, babbitt alloy is usually used in combination with a matrix material to produce bushings with excellent performance.

[0003] At present, the main preparation processes of tin-based babbitt alloys include various traditional processes such as casting, spraying and welding. However, these processes have limited success in improving the wear resistance, hardness and bonding strength of tin-based babbitt alloys with the substrate. Laser cladding technology uses a high-energy laser beam as a heat source to quickly heat and melt the powder or wire and the substrate surface, with the advantages of low dilution rate and high cladding efficiency. Compared with traditional cladding processes, this technology can achieve a surface coating with high metallurgical bonding strength and excellent performance. At the same time, due to the small heat input, the deformation of the substrate can be kept low. Not only does it have a wide range of powder material choices, but it also has a high degree of automation and stable and reliable processing quality. Therefore, it is widely used in aerospace, metallurgy, rail transportation and other fields.

[0004] In actual working scenarios, due to the combined effects of friction and shear stress, bearings often face serious wear risks, and may even fall off, leading to bearing failure. Reducing the friction coefficient of bearings, enhancing their hardness, and optimizing their tribological properties are all indispensable measures. The patent with publication number CN202010599227.8 discloses a method for improving the wear resistance of tin-based babbitt alloys, and the spray powder is composed of the following by mass percentage: 60-90% tin-based babbitt alloy powder, 5-25% nickel alloy powder, and 5-15% metal TiO2 powder. The mixed powders prepared in different proportions are sprayed on H62 brass, and the wear resistance of the prepared spray layer is improved. The patent with publication number CN202010596308.2 discloses a method for preparing a tin-based babbitt alloy containing TiN and TiO2, and the spray powder is prepared by mixing 5-15% titanium oxide powder, 5-15% metal TiN powder, and 70-90% tin-based babbitt alloy powder. The friction coefficient of the plasma sprayed tin-based babbitt alloy layer containing TiN and TiO2 is 3.3 times lower than that of the pure tin-based babbitt alloy coating. In general, adding alloy elements or particle phases to tin-based babbitt alloy powder can achieve the purpose of improving its wear resistance.

[0005] The present invention provides a method for preparing a Ti-added laser cladding tin-based babbitt alloy coating. The Ti element is added to the tin-based babbitt alloy powder to refine the hard phase and improve the wear resistance of the coating. This has important application value for alleviating the wear condition of the bearing bush, effectively preventing the shedding phenomenon, thereby extending the service life of the bearing bush and ensuring the stable operation of the bearing system. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a tin-based babbitt alloy laser cladding coating with added Ti element, to obtain tin-based babbitt alloy powder suitable for laser cladding, and to enhance and improve the performance of the tin-based babbitt alloy, so as to solve the problem mentioned in the background technology that the babbitt alloy has low hardness, wear resistance and bonding strength, and is prone to severe wear or even shearing of the bearing under working conditions due to the combined effect of friction and shear stress, thereby causing bearing failure.

[0007] To achieve the above object, the present invention provides a method for preparing a Ti-added tin-based babbitt alloy laser cladding coating, comprising the following steps:

[0008] S1, adding a certain proportion of metal Ti powder to tin-based babbitt alloy powder, and adding the obtained metal Ti powder and tin-based babbitt alloy powder into a mixer for mixing, and mixing for 5-6 hours to obtain a mixed powder containing Ti element;

[0009] S2, select 20 steel with a size of 150mm×150mm×10mm as the substrate, use a coaxial powder feeding laser to evenly clad the mixed powder of tin-based babbitt alloy powder and metal Ti powder on the surface of the 20 steel to obtain a titanium-containing tin-based babbitt alloy coating.

[0010] Preferably, in S1, the mass percentage of Ti powder in the mixed powder is 0-3.0%.

[0011] Preferably, in S1, the tin-based babbitt alloy powder includes Sn-11Sb-6Cu babbitt alloy powder, the powder particle size is 45-105μm, the powder composition is Cu5.5%-6.5%, Sb11.5%-12.0%, and Sn is the remainder; the average particle size of the metal Ti powder particles is 45-105μm.

[0012] Preferably, in S2, before the laser cladding test, the substrate surface is polished and bright using sandpapers of 80 mesh, 120 mesh, 400 mesh, 800 mesh, and 1200 mesh in sequence, and then the substrate surface is cleaned with ethanol, and the Ti-containing tin-based babbitt alloy powder mixed in a certain proportion is placed in a vacuum drying oven and dried for 4-6 hours.

[0013] Preferably, in S2, a coaxial powder feeding laser cladding method is adopted, high-purity argon is used as the shielding gas, the laser model is TruDisk12003, the spot diameter is 3mm, the powder feeding speed is 0.4-0.6r / min, the overlap rate is 40-50%, the laser power is 1400-1800W, the scanning speed is 10-14mm / s, the shielding gas flow rate is 10-15L / min, and the single layer coating thickness is about 0.5-0.7mm.

[0014] Preferably, a wire cutting machine is used to cut the coating to obtain a cross-sectional sample, and a metallographic mounting machine is used to prepare a mounted sample, and the sample is ground using 80 mesh, 120 mesh, ... 1500 mesh, and 2000 mesh sandpaper in sequence, and then the sample is polished and corroded, and the microstructure is observed and recorded using a metallographic microscope.

[0015] Preferably, a wire cutting machine is used to cut a surface sample with a size of 10mm×10mm×10mm, which is then ground and polished in sequence, and a wear test is performed using a CFI-1 wear tester with a loading load of 3N, a rotation radius of 3mm, a rotation speed of 150r / min, and a wear time of 20min; an Rtec three-dimensional surface profiler is used to perform three-dimensional morphology of the wear scar surface to obtain the surface profile of the wear scar for calculating the wear rate.

[0016] Beneficial effects: The present invention adds metal Ti powder to the tin-based babbitt alloy powder and clads the mixture on the surface of 20 steel. The obtained Ti-containing tin-based babbitt alloy coating has a dense structure, a refined and uniformly distributed white hard phase, and a good metallurgical bonding between the coating and the substrate. The friction and wear test of the cladding sample shows that the friction coefficient of the tin-based babbitt alloy coating without adding Ti is μ=0.494, and the wear rate is 0.143×10 -6 mm 3 / N·m. With the addition of Ti element, the friction coefficient and wear rate of the tin-based babbitt alloy coating gradually decrease. When 1.6% Ti content is added, the friction coefficient μ=0.391 and the wear rate 0.035×10 -6 mm 3 / N·m, indicating that after adding Ti element, the Sn-based Babbitt alloy coating exhibits better wear resistance and is more suitable for the preparation of Sn-based Babbitt alloy coating by laser cladding method. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a microstructure diagram of the tin-based babbitt alloy coating prepared in Example 1 of the present invention;

[0018] Figure 2 This is a microstructure diagram of the titanium-containing tin-based babbitt alloy coating prepared in Example 2 of the present invention;

[0019] Figure 3 This is a microstructure diagram of the titanium-containing tin-based babbitt alloy coating prepared in Example 3 of the present invention;

[0020] Figure 4 This is a microstructure diagram of a titanium-containing tin-based babbitt alloy coating prepared in Example 4 of the present invention;

[0021] Figure 5 The friction coefficient diagram of the titanium-containing tin-based babbitt alloy coating prepared in Examples 1-4 of the present invention;

[0022] Figure 6 This is a wear rate diagram of the titanium-containing tin-based babbitt alloy coating prepared in Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments:

[0024] Example 1

[0025] like Figure 1 As shown, a method for preparing a tin-based babbitt alloy laser cladding coating comprises the following specific steps:

[0026] First, the tin-based babbitt alloy powder is placed in a vacuum drying oven and dried for 4-6 hours.

[0027] 20 steel with a size of 150 mm × 150 mm × 10 mm was selected as the substrate. Before the laser cladding test, the substrate surface was polished smooth using 80 mesh, 120 mesh, 400 mesh, 800 mesh, and 1200 mesh sandpaper in sequence, and then the substrate surface was cleaned with ethanol.

[0028] The tin-based babbitt alloy coating was obtained by coaxial powder feeding laser cladding with high-purity argon as the protective gas.

[0029] The laser model used for laser cladding is TruDisk12003, and the spot diameter is The powder feeding speed is 0.6r / min, the overlap rate is 50%, the laser power is 1400W, the scanning speed is 10-14mm / s, the shielding gas flow rate is 10L / min, and the single-layer cladding thickness is about 0.6mm.

[0030] The coating was cut by a wire cutting machine to obtain cross-sectional samples, and a metallographic mounting machine was used to prepare mounted samples. The samples were ground using 80-mesh, 120-mesh, 1500-mesh, and 2000-mesh sandpapers in sequence, and then polished and corroded. The microstructure was observed and recorded using a metallographic microscope.

[0031] A wire cutting machine was used to cut surface samples with a size of 10mm×10mm×10mm, and they were ground and polished in sequence. A wear test was carried out using a CFI-1 wear tester with a loading load of 3N, a rotation radius of 3mm, a rotation speed of 150r / min, and a wear time of 20min. An Rtec 3D surface profiler was used to perform three-dimensional morphology of the wear scar surface to obtain the surface profile of the wear scar for calculating the wear rate.

[0032] Example 2

[0033] like Figure 2 As shown, a method for preparing a tin-based babbitt alloy laser cladding coating with Ti element added comprises the following specific steps:

[0034] Firstly, metal Ti powder is added to the tin-based babbitt alloy powder, wherein the added amount of Ti powder is 0.8% by mass. The tin-based babbitt alloy powder and the metal Ti powder are added to the mixture for mixing. After mixing for 6 hours, a mixed powder is obtained. The mixed powder and the mixed tin-based babbitt alloy powder containing Ti are placed in a vacuum drying oven and dried for 4-6 hours.

[0035] 20 steel with a size of 150 mm × 150 mm × 10 mm was selected as the substrate. Before the laser cladding test, the substrate surface was polished smooth using 80 mesh, 120 mesh, 400 mesh, 800 mesh, and 1200 mesh sandpaper in sequence, and then the substrate surface was cleaned with ethanol.

[0036] The tin-based babbitt alloy coating with titanium added was obtained by coaxial powder feeding laser cladding with high-purity argon as the protective gas.

[0037] The laser model used for laser cladding is TruDisk12003, and the spot diameter is The powder feeding speed is 0.6r / min, the overlap rate is 50%, the laser power is 1400W, the scanning speed is 10-14mm / s, the shielding gas flow rate is 10L / min, and the single-layer cladding thickness is about 0.6mm.

[0038] The coating was cut by a wire cutting machine to obtain cross-sectional samples, and a metallographic mounting machine was used to prepare mounted samples. The samples were ground using 80-mesh, 120-mesh, 1500-mesh, and 2000-mesh sandpapers in sequence, and then polished and corroded. The microstructure was observed and recorded using a metallographic microscope.

[0039] A wire cutting machine was used to cut surface samples with a size of 10mm×10mm×10mm, and they were ground and polished in sequence. A wear test was carried out using a CFI-1 wear tester with a loading load of 3N, a rotation radius of 3mm, a rotation speed of 150r / min, and a wear time of 20min. An Rtec 3D surface profiler was used to perform three-dimensional morphology of the wear scar surface to obtain the surface profile of the wear scar for calculating the wear rate.

[0040] Example 3

[0041] like Figure 3 As shown, a method for preparing a tin-based babbitt alloy laser cladding coating with Ti element added comprises the following specific steps:

[0042] Firstly, metal Ti powder is added to the tin-based babbitt alloy powder, wherein the mass percentage of the added Ti powder is 1.2%; both the tin-based babbitt alloy powder and the metal Ti powder are added to the mixture for mixing, and mixed for 6 hours to obtain a mixed powder; and the mixed tin-based babbitt alloy powder containing Ti is placed in a vacuum drying oven and dried for 4-6 hours.

[0043] 20 steel with a size of 150 mm × 150 mm × 10 mm was selected as the substrate. Before the laser cladding test, the substrate surface was polished smooth using 80 mesh, 120 mesh, 400 mesh, 800 mesh, and 1200 mesh sandpaper in sequence, and then the substrate surface was cleaned with ethanol.

[0044] The tin-based babbitt alloy coating with titanium added was obtained by coaxial powder feeding laser cladding with high-purity argon as the protective gas.

[0045] The laser model used for laser cladding is TruDisk12003, and the spot diameter is The powder feeding speed is 0.6r / min, the overlap rate is 50%, the laser power is 1400W, the scanning speed is 10-14mm / s, the shielding gas flow rate is 10L / min, and the single-layer cladding thickness is about 0.6mm.

[0046] The coating was cut by a wire cutting machine to obtain cross-sectional samples, and a metallographic mounting machine was used to prepare mounted samples. The samples were ground using 80-mesh, 120-mesh, 1500-mesh, and 2000-mesh sandpapers in sequence, and then polished and corroded. The microstructure was observed and recorded using a metallographic microscope.

[0047] A wire cutting machine was used to cut surface samples with a size of 10mm×10mm×10mm, and they were ground and polished in sequence. A wear test was carried out using a CFI-1 wear tester with a loading load of 3N, a rotation radius of 3mm, a rotation speed of 150r / min, and a wear time of 20min. An Rtec 3D surface profiler was used to perform three-dimensional morphology of the wear scar surface to obtain the surface profile of the wear scar for calculating the wear rate.

[0048] Example 4

[0049] like Figure 4 As shown, a method for preparing a tin-based babbitt alloy laser cladding coating with Ti element added comprises the following specific steps:

[0050] Firstly, metal Ti powder is added to the tin-based babbitt alloy powder, wherein the mass percentage of the added Ti powder is 1.6%. The tin-based babbitt alloy powder and the metal Ti powder are added to the mixture for mixing. After mixing for 6 hours, a mixed powder is obtained; and the mixed tin-based babbitt alloy powder containing Ti is placed in a vacuum drying oven and dried for 4-6 hours.

[0051] 20 steel with a size of 150 mm × 150 mm × 10 mm was selected as the substrate. Before the laser cladding test, the substrate surface was polished smooth using 80 mesh, 120 mesh, 400 mesh, 800 mesh, and 1200 mesh sandpaper in sequence, and then the substrate surface was cleaned with ethanol.

[0052] The tin-based babbitt alloy coating with titanium added was obtained by coaxial powder feeding laser cladding with high-purity argon as the protective gas.

[0053] The laser model used for laser cladding is TruDisk12003, and the spot diameter is The powder feeding speed is 0.6r / min, the overlap rate is 50%, the laser power is 1400W, the scanning speed is 10-14mm / s, the shielding gas flow rate is 10L / min, and the single-layer cladding thickness is about 0.6mm.

[0054] The laser cladding coating was cut by a wire cutting machine to obtain cross-sectional samples, and a metallographic mounting machine was used to prepare the mounted samples. The samples were ground with 80-mesh, 120-mesh, 1500-mesh, and 2000-mesh sandpapers in sequence, and then polished and corroded. The microstructure was observed and recorded using a metallographic microscope.

[0055] A wire cutting machine was used to cut surface samples with a size of 10mm×10mm×10mm, and they were ground and polished in sequence. A wear test was carried out using a CFI-1 wear tester with a loading load of 3N, a rotation radius of 3mm, a rotation speed of 150r / min, and a wear time of 20min. An Rtec 3D surface profiler was used to perform three-dimensional morphology of the wear scar surface to obtain the surface profile of the wear scar for calculating the wear rate.

[0056] Based on the above embodiments, it can be found that as the amount of Ti element added increases, the white block phase in the coating is significantly refined and distributed more evenly, and the number of distributed white precipitated phases is greater.

[0057] Figure 5 and Figure 6 They are respectively the friction coefficient diagrams and wear rate diagrams of Examples 1 to 4, and the test results are shown in Table 1.

[0058] Table 1 shows the friction coefficient and wear rate of Examples 1 to 4.

[0059]

[0060]

[0061] It can be seen from the test results in Table 1 that with the addition of Ti element, the friction coefficient and wear rate of the coating both decrease. When 1.6wt% Ti is added, the tin-based babbitt alloy coating exhibits a friction coefficient μ = 0.391 and a wear rate of 0.035×10 - 6 mm 3 / (N·m), the wear resistance is significantly improved.

[0062] Although the embodiments of the present invention have been shown and described, those skilled in the art can make various adjustments, improvements, substitutions and innovations to these embodiments based on their understanding and compliance with the core concepts and spirits of the present invention. Therefore, the protection scope of the present invention shall be defined by the attached claims and their equivalents.

Claims

1. A method for preparing a Ti-added tin-based babbitt alloy laser cladding coating, characterized in that: The following steps are involved: S1, adding metal Ti powder to tin-based babbitt alloy powder, and adding the obtained metal Ti powder and tin-based babbitt alloy powder into a mixer to mix, and after mixing for 5-6 hours, a mixed powder containing Ti element is obtained; S2, select 20 steel with a size of 150mm×150mm×10mm as the substrate, use a coaxial powder feeding laser to evenly clad the mixed powder of tin-based babbitt alloy powder and metal Ti powder on the surface of the 20 steel to obtain a titanium-containing tin-based babbitt alloy coating.

2. The method for preparing a Ti-added tin-based babbitt alloy laser cladding coating according to claim 1, characterized in that: In S1, the mass percentage of Ti powder in the mixed powder is 0-3.0%.

3. The method for preparing a Ti-added tin-based babbitt alloy laser cladding coating according to claim 2, characterized in that: In S1, the tin-based babbitt alloy powder includes Sn-11Sb-6Cu babbitt alloy powder, the powder particle size is 45-105μm, the powder composition is Cu5.5%-6.5%, Sb11.5%-12.0%, and Sn is the remainder; the average particle size of the metal Ti powder particles is 45-105μm.

4. The method for preparing a Ti-added tin-based babbitt alloy laser cladding coating according to claim 3, characterized in that: In S2, before the laser cladding test, the substrate surface was polished with sandpapers of 80 mesh, 120 mesh, 400 mesh, 800 mesh, and 1200 mesh in sequence, and then the substrate surface was cleaned with ethanol, and the mixed Ti-containing tin-based babbitt alloy powder was placed in a vacuum drying oven and dried for 4-6 hours.

5. The method for preparing a Ti-added tin-based babbitt alloy laser cladding coating according to claim 4, characterized in that: In S2, a coaxial powder feeding laser cladding method is adopted, high-purity argon is used as the protective gas, the laser model is TruDisk12003, the spot diameter is 3mm, the powder feeding speed is 0.4-0.6r / min, the overlap rate is 40-50%, the laser power is 1400-1800W, the scanning speed is 10-14mm / s, the protective gas flow rate is 10-15L / min, and the single layer coating thickness is about 0.5-0.7mm.

6. The method for preparing a Ti-added tin-based babbitt alloy laser cladding coating according to claim 5, characterized in that: The coating was cut by a wire cutting machine to obtain cross-sectional samples, and a metallographic mounting machine was used to prepare mounted samples. The samples were ground using 80-mesh, 120-mesh, 1500-mesh, and 2000-mesh sandpapers in sequence, and then polished and corroded. The microstructure was observed and recorded using a metallographic microscope.

7. The method for preparing a Ti-added tin-based babbitt alloy laser cladding coating according to claim 6, characterized in that: A wire cutting machine was used to cut surface samples with a size of 10mm×10mm×10mm, and they were ground and polished in sequence. A wear test was carried out using a CFI-1 wear tester with a loading load of 3N, a rotation radius of 3mm, a rotation speed of 150r / min, and a wear time of 20min. An Rtec 3D surface profiler was used to perform three-dimensional morphology of the wear scar surface to obtain the surface profile of the wear scar for calculating the wear rate.

Citation Information

Patent Citations

  • A method for improving the wear resistance of tin-based Babbitt alloys

    CN111560578B

  • Preparation method of tin-based babbitt coating containing TiN and TiO2

    CN111575628A

Cited By

  • Laser cladding process method for improving hardness, wear resistance and metallurgical bonding strength based on S element

    CN121992304A